Study of teh D.C conductance mechanism of evaporated amorphous silicon films - Atağ, Yılmaz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In this thesis the d.c bulk characteristis of amorphous silicon films are investigated. The films are prepared by electron gun evaporation in a conventional vacuum system. Ohmic contacts are established between the silicon films and the aluminum electrodes. I-V and I-T measurements are performed in the temperaturege range, 110°K to 430°K. Room temperature measurements show that the preparation conditions such as evaporation rate, aging and subsequent annealing all affect the d.c conductivities of the films. In the low temperature range, the data analyzed with the existing models of amorphous semiconductors and the density of states near the Fermi level is calculated. The high temperature data are used to calculate the mobility gap of the amorphous silicon film. The results are then compared with the previously published work.
Keywords: Amorphous semiconductors.; Electric conductivity.